2021
DOI: 10.3389/fpls.2021.691833
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genomes of Acanthochlamys bracteata (China) and Xerophyta (Africa) (Velloziaceae): Comparative Genomics and Phylogenomic Placement

Abstract: Acanthochlamys P.C. Kao is a Chinese endemic monotypic genus, whereas XerophytaJuss. is a genus endemic to Africa mainland, Arabian Peninsula and Madagascar with ca.70 species. In this recent study, the complete chloroplast genome of Acanthochlamys bracteata was sequenced and its genome structure compared with two African Xerophyta species (Xerophyta spekei and Xerophyta viscosa) present in the NCBI database. The genomes showed a quadripartite structure with their sizes ranging from 153,843 bp to 155,498 bp, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 98 publications
3
16
0
Order By: Relevance
“…We found that the GC content in the cp genome of Pooideae species was unevenly distributed, with the IR regions having a higher GC content than the two single copy regions. This may be attributed to the fact that four rRNA genes with high GC content were located in the IR regions, which supported the speculation of previous studies ( Mardanov et al, 2008 ; Gao et al, 2009 ; Wanga et al, 2021 ). The accD gene has been lost within the cp genomes of Pooideae species, while ycf1 , ycf2 , ycf15 , and ycf68 were pseudogenes, which is a relatively common phenomenon in Poaceae ( Huang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…We found that the GC content in the cp genome of Pooideae species was unevenly distributed, with the IR regions having a higher GC content than the two single copy regions. This may be attributed to the fact that four rRNA genes with high GC content were located in the IR regions, which supported the speculation of previous studies ( Mardanov et al, 2008 ; Gao et al, 2009 ; Wanga et al, 2021 ). The accD gene has been lost within the cp genomes of Pooideae species, while ycf1 , ycf2 , ycf15 , and ycf68 were pseudogenes, which is a relatively common phenomenon in Poaceae ( Huang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…These similarities in codon choice also reveal the related relationship in the four species. The observed codon pattern is consistent with the CP genomes of Amomum [68], Panax [69], Dipterygium and Cleome [70], and various other species [71][72][73].…”
Section: S3supporting
confidence: 82%
“…Codon is the connection between the nucleic acids and proteins, and codon usage reflects the preference for selective use of codons encoding specific amino acids with genetic information ( Wanga et al, 2021 ). The codon usage frequency of 79 protein-coding genes for 8 Fagopyrum species were calculated, and 64 codons were involved in encoding proteins containing three termination codons, such as UAA, UAG, and UGA ( Table 3 ).…”
Section: Results and Analysismentioning
confidence: 99%